Carbon Loss in Chicken Litter Compost As Affected By Carbon to Nitrogen Ratio and Turning Frequency - Ogunwande, G.A. (Ife Journal of Technology, 2011)
Raw chicken manure was co-composted with sawdust in turned-windrow piles to study the effects of carbon to nitrogen (C:N) ratio and turning frequency (TF) on the loss of total carbon (C) during composting. Three levels of C:N ratio (20:1, 25:1 and 30:1) and TF (2, 4 and 6 days) were experimented in a two-factor completely randomized block design. During the composting process, temperature, pH, moisture content (MC), total C, phosphorus (P), potassium (K) and nitrogen (N), dry matter (DM) and C:N ratio were monitored. Also, MC of the piles was periodically replenished to 55%. The results showed that both C:N ratio and TF had significant (p ≤ 0.05) effect on temperature, pH, total N, C, P and K losses and C:N ratio of the piles while only C:N ratio affected (p ≤ 0.05) DM losses. It was observed that moisture loss increased as C:N ratio and TF increased. The decline of pile temperatures to near ambient temperature occurred at about 87 days in all treatments. The final total C losses ranged between 63.1 and 83.8%, with 65.2-97.1% occurring within the first six weeks when the pile temperatures and pH values were above 33 oC and 7.7, respectively. The total C losses were largely attributed to organic matter degradation and increased as C:N ratio and TF increased. The combined effects of C:N ratio and TF showed that treatment with 6 days TF and C:N ratio of 20:1 had the minimum total C loss (63.1%).